Risk of spontaneous preterm birth in singleton pregnancies conceived after IVF/ICSI treatment: meta‐analysis of cohort studies. (3rd January 2018) - Cavoretto, P.; Candiani, M.; Giorgione, V.; Inversetti, A.; Abu‐Saba, M. M.; Tiberio, F.; Sigismondi, C.; Farina, A.
ABSTRACT: Objective: Preterm birth (PTB) is more common in pregnancies conceived by in‐vitro fertilization (IVF) as compared with those conceived naturally. However, the extent to which this is attributed to spontaneous labor or to iatrogenic indications has not been determined. The aim of this study was to quantify the risk of spontaneous PTB (sPTB) in singleton pregnancies resulting from IVF or intracytoplasmic sperm injection (ICSI) treatment as compared with that in spontaneously conceived pregnancies. Methods: An electronic search of PubMed/MEDLINE, Scopus and Web of Science to September 2017 and manual search of reference lists identified articles comparing the risk of sPTB in IVF/ICSI vs spontaneously conceived singleton pregnancies. Inclusion criteria were singleton conception with IVF/ICSI, PTB defined as delivery before 37 weeks' gestation and cohort design with clear distinction between spontaneous and indicated PTB. The primary outcome was sPTB < 37 weeks. Relevant secondary outcomes were also analyzed, including sPTB < 34 and < 32 weeks, preterm prelabor rupture of membranes, stillbirth, perinatal mortality, neonatal sepsis, respiratory distress syndrome and gastrointestinal morbidity. A meta‐analysis provided the estimation of risk of sPTB in IVF/ICSI pregnancies. Results: In total, 674 records were identified from the search, of which 15 met the inclusion criteria and were included in the meta‐analysis. A pooled crude analysis of the primary outcome generated a total sample size of 61 677 births, including 8044 singletons conceived after IVF/ICSI and 53 633 conceived spontaneously. A pooled crude data analysis showed a significant increase in the incidence of sPTB < 37 weeks in singleton IVF/ICSI pregnancies compared with those conceived spontaneously (810/8044 (10.1%) vs 2932/53 633 (5.5%); odds ratio (OR), 1.75; 95% CI, 1.50–2.03; I 2  = 39%). A subgroup analysis of studies matching for maternal age and parity confirmed the finding (OR, 1.63; 95% CI, 1.30–2.05; I 2  = 33%). A pooled crude analysis of secondary outcomes showed a significant increase in the incidence of sPTB < 34 weeks in pregnancies conceived after IVF/ICSI compared with those conceived spontaneously (37/1012 (3.6%) vs 24/1107 (2.2%); OR, 1.78; 95% CI, 1.03–3.08; I 2  = 6%) and did not show any significant difference for any of the other secondary outcomes analyzed. The quality of evidence, rated using the GRADE criteria, was low for the outcome sPTB < 37 weeks and very low for sPTB < 34 weeks. Conclusions: The risk of sPTB in singleton pregnancies resulting from IVF/ICSI is significantly greater than that in spontaneously conceived singletons. These findings should be interpreted with caution given the low quality of the available evidence. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.